Bringing successful aging theories to occupational practice: Is selective optimization with compensation trainable? - Müller, Andreas; Herbst, Kirsten; Maatouk, Imad (Work, aging and retirement, 2018)
Selective optimization with compensation (SOC) is regarded as a powerful action strategy to cope with age-related changes in resources. Occupational interventions based on SOC might therefore make an important contribution to successful aging at work. However, SOC interventions at work are scarce. Against this background we investigated (a) whether employees can be trained with SOC, (b) whether job characteristics (job autonomy, job demands) and individual resources (job experience, self-efficacy), and chronological age moderate the effects of the intervention on SOC. We conducted 3 randomized controlled interventions among 253 nurses (chronological age 22-64 years). One hundred twenty-nine nurses were randomized to trainings that involved exercise of SOC-behaviors (intervention group, IG) and 124 were randomized to the control group (CG). Results: (a) The interventions showed a significant overall positive effect on SOC. (b) There was a significant positive effect of the intervention on SOC when job demands are low. There were no such moderating effects of job autonomy, job experience, self-efficacy, and chronological age. Our findings indicate that employees can be trained to use SOC-strategies at work. High job demands can impair the training effects, which indicate that the initial acquisition of SOC requires resources.